EUS-guided FNA of a portal vein thrombus in hepatocellular carcinoma - Kayar, Yusuf (Pan Afr Med J, 2015)
Portal vein thrombosis is a relatively rare but well-known complication of cirrhosis that has a prevalence of between 1% and 5.7%. On the contrary, in case of hepatocellular carcinoma (HCC), it is a much more frequent complication. In this paper, we presented three cases that had liver cirrhosis, mass and portal vein thrombosis in liver. We were not able to diagnose the cases through imaging methods, laboratory results or histopathologically, however, they were diagnosed with endoscopic ultrasonography- fine needle aspiration EUS-FNA from portal vein thrombus.